Development of WS2/MXene (Ti3C2Tx) nanohybrid based multi-functional textronic sensor for non-invasive personal healthcare monitoring. (1st March 2023) - Adepu, Vivek; Tathacharya, Manav; Mattela, Venkat; Sahatiya, Parikshit
Abstract: This report demonstrates the development of a WS2 /Ti3 C2 T X nanohybrid-based multifunctional physical sensor (pressure, strain, and humidity) on a textile cloth. The fabricated sensor demonstrates excellent sensitivity and gauge factor of 3.66198 kPa −1, 3.17119, and 1.61787 towards pressure, strain, and humidity stimuli, respectively, with exceptional long-term stability showing an insignificant change in performance over ∼4000 and ∼4200 cycles. The underlying transduction mechanism for the fabricated piezoresistive multifunctional physical sensor is explained utilizing the intrinsic piezoresistive effect as well as the modulation of the Schottky barrier height exhibited by the WS2 /Ti3 C2 T x at the local heterojunctions with the help of detailed band structures that are realized by ultraviolet photoelectron spectroscopy. A smartphone-based application was established to authenticate wireless incorporation of the fabricated multifunctional physical sensors to demonstrate applications such as tetraplegic call detection, mood detection, and dry/wet skin monitoring system. The successful demonstration of connected healthcare applications using the WS2 /Ti3 C2 T x multifunctional sensor opens up new possibilities and applications in the fields of smart healthcare, e-textiles, and flexible electronics.